Invisible work: Child work in households with a person living with HIV/AIDS in Central Uganda - Abimanyi-Ochom, Julie (SAHARA J, 2017)
Background: HIV/AIDS has led to increased mortality and morbidity, negatively impacting adult labour especially in HIV/AIDS burdened Sub-Saharan Africa. There has been some exploration of the effects of HIV/AIDS on paid child labour, but little empirical work on children’s non-paid child work. This paper provides quantitative evidence of how child and household-level factors affect children’s involvement in both domestic and family farm work for households with a person living with HIV/AIDS (PLWHA) compared to non-PLWHA households using the 2010/2011 Centre for Health Economics Uganda HIV questionnaire Survey. Method: Descriptive analysis and multivariate logistic modelling is used to explore child and household-level factors that affect children’s work participation. Results: This research reveals greater demands on the labour of children in PLWHA households in terms of family farm work especially for boys. Results highlight the expected gendered social responsibilities within the household space, with girls and boys engaged more in domestic and family farm work, respectively. Girls shared a greater proportion of household financial burden by working more hours in paid work outside the household than boys. Lastly, the study revealed that a household head’s occupation increases children’s participation in farm work but had a partial compensatory effect on their involvement in domestic work. Wealth and socio-economic standing is no guarantee to reducing child work. Conclusion: Children from PLWHA households are more vulnerable to child work in family farm work especially boys; and girls are burdened beyond the household space through paid work. Differing perspectives and solutions need to consider the contextual nature of child work.